2018
DOI: 10.1016/j.bjid.2017.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polymyxin B-containing regimens on renal function for the treatment of carbapenem-resistant Enterobacteriacea mediastinitis

Abstract: A retrospective cohort study, were evaluated: polymyxin B plus aminoglycosides or polymyxin B plus other antibiotics. Any degree of acute kidney injury occurred in 26 (86.6%) patients. The median time to acute kidney injury was 6.0 (95% CI 3-14) days in the polymyxin-aminoglycoside containing regimen group, against 27.0 (95% CI 6-42) days in the polymyxin with other antimicrobial combinations group (p=0.03). Polymyxin B with aminoglycosides group progressed faster to any degree of renal dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Polymyxins, an old class of cationic antibiotics have become an important last-line treatment for MDR Gramnegative bacteria (Nang et al, 2021). Nevertheless, its early application in clinical setting was restrained due to the nephrotoxicity and neurotoxicity cases reported (Durante-Mangoni et al, 2016;Abboud et al, 2018). In addition, pharmacokinetics/pharmacodynamics (PK/PD) data showed that polymyxin monotherapy may lead to treatment failure as it is not always possible to obtain reliably in vivo efficacious plasma exposure (Pogue et al, 2017;Landersdorfer et al, 2018) along with the potential emergence of heteroresistant sub-population (Bergen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Polymyxins, an old class of cationic antibiotics have become an important last-line treatment for MDR Gramnegative bacteria (Nang et al, 2021). Nevertheless, its early application in clinical setting was restrained due to the nephrotoxicity and neurotoxicity cases reported (Durante-Mangoni et al, 2016;Abboud et al, 2018). In addition, pharmacokinetics/pharmacodynamics (PK/PD) data showed that polymyxin monotherapy may lead to treatment failure as it is not always possible to obtain reliably in vivo efficacious plasma exposure (Pogue et al, 2017;Landersdorfer et al, 2018) along with the potential emergence of heteroresistant sub-population (Bergen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%